2018
DOI: 10.4018/ijswis.2018010105
|View full text |Cite
|
Sign up to set email alerts
|

Prose

Abstract: The study of paraconsistent reasoning with ontologies is especially important for the Semantic Web since knowledge is not always perfect within it. However, classical OWL reasoners cannot support reasoning with inconsistent ontologies. In this article, the authors present a plugin-based framework called prose to provide rich paraconsistent reasoning services for OWL ontologies, whose architecture contains the three following parts: a classical OWL reasoner, a multi-valued transformer, and an OWL API connecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The implementation of this framework is beyond this paper. There are some paraconsistent reasoners with ontologies such as ParOWL [ 43 ], PROSE [ 26 , 30 ], and QC-OWL [ 47 ]. In this paper, we have developed a new tableaux for multi-valued DLs and showed that the tableau is sound and complete for the minimally inconsistent DL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of this framework is beyond this paper. There are some paraconsistent reasoners with ontologies such as ParOWL [ 43 ], PROSE [ 26 , 30 ], and QC-OWL [ 47 ]. In this paper, we have developed a new tableaux for multi-valued DLs and showed that the tableau is sound and complete for the minimally inconsistent DL.…”
Section: Discussionmentioning
confidence: 99%
“…Our minimally inconsistent DL satisfies some useful properties, such as disjunctive syllogism (DS), resolution and non-monotonicity (see Table 2 ) which are failed by those paraconsistent DLs based on multi-valued DLs. The quasi-classical DL in [ 26 , 28 , 30 ] is a major variant of paraconsistent DLs, in which two semantics, namely weak semantics and strong semantics, are introduced to characterize quasi-classical semantics so that DS and resolution valid. There are some similarities and differences between minimally inconsistent semantics and quasi-classical semantics.…”
Section: Related Workmentioning
confidence: 99%